(untitled) (Studia theodisca, 2018)
In Der abenteuerliche Simplicissimus (1668) Grimmelshausen depicts the Hungarian Hutterites as an ideal society, focusing predominantly on the ethics and social structure of this communal branch of Anabaptism. In this critical reading, I explore how Grimmelshausen fictionalized the religious minority, its commitment to particular social structures and ethical aspects, and its separation from society. As part of this analysis, the study investigates which social and religious principles drawn from polemical accounts and contemporary sources influence and counter the minority’s image as an ideal society and how this image of the religious group supports the novel’s notion of utopia.